Situational and Positional Effects on the Technical Variation of Players in the UEFA Champions League - Yi, Qing; Gómez, Miguel-Ángel; Liu, Hongyou; Gao, Binghong; Wunderlich, Fabian; Memmert, Daniel (Frontiers in Psychology, 2020)
This study aimed to identify the situational and positional effects on the variation of players’ technical performance in the UEFA Champions League from a long-term perspective. The technical performance of full match observations from outfield players in the UEFA Champions League from season 2009/10 to 2016/17 was analysed. The coefficient of variation of each variable of each player in each season was calculated to evaluate the match-to-match variation of technical performance. The variation of technical performance between players was compared across five playing positions and five situational variables using the non-clinical magnitude-based inference. Results showed that variables related to goal scoring, passing and organising from five playing positions showed a relatively higher variation among five competing contexts (ES: -0.72±0.38-0.82±0.61). Quality of team, quality of opponent and match outcome showed relatively greater influences than competition stage and match location on the variation of player’s technical performance (ES: -0.72±0.38-0.57±0.56). The technical performances of wide players (full backs and wide midfielders) were more variable between the group and knockout stage (ES: -0.37±0.32-0.28±0.19). This study provides an important understanding of the associations among the variation of technical indicators, playing positions and situational variables. These profiles of technical variation could be used by coaches and analysts for talent identification, player recruitment, pre-match preparation, and post-match evaluation.